Pengembangan Usaha Mikro Kecil Menengah (UMKM) Berbasis Agribisnis Di Kelurahan Gunung Anyar Tambak - Dyan Fransiska Agata; Dimas Aditya Rama; Praja Firdaus Nuryanda; Noor Rizkiyah (Jurnal Pelayanan dan Pengabdian Masyarakat Indonesia, 2023)
MSMEs in Surabaya reached around 60 thousand in 2022. Meanwhile, the number of MSMEs in the culinary or agribusiness sector is around 25 thousand. According to this large number, MSMEs owners are required to have their own advantages characteristics. The strategy that can be applied to increase the competitiveness of an MSME is through branding. The implementation of this community service aims to develop and improve the competitiveness of MSMEs through branding mentoring. This research uses survey, socialization, analysis, and branding methods. The result of this community service are that MSMEs are helped by the implementation of branding, such as logos, product photos, and taglines. So that these MSMEs are more easily recognized and attract consumers and can increase competitiveness and sales.